ECONOMIC THOUGHTS OF YUSUF KHOS KHOJIB - Asrakulova Adiba Nabievna (Web of Journals Publishing, 2025)
This article discusses in detail the relationship between the state and the population on economic issues, the issues of getting the country out of economic crisis, and the issues of economic development of the state in the work of Yusuf Khos Khajib “Kutadgu Bilig”.
Keywords: Country, population, interest, economy, crisis, profit, work, idea, law, city, era, statesman.